Intracellular trafficking of AIP56, an NF-κB-cleaving toxin from Photobacterium damselae subsp. Piscicida - Pereira, LM (2014)
AIP56 (apoptosis-inducing protein of 56 kDa) is a metalloprotease AB toxin secreted by Photobacterium damselae subsp. piscicida that acts by cleaving NF-κB. During infection, AIP56 spreads systemically and depletes phagocytes by postapoptotic secondary necrosis, impairing the host phagocytic defense and contributing to the genesis of infection-associated necrotic lesions. Here we show that mouse bone marrow-derived macrophages (mBMDM) intoxicated by AIP56 undergo NF-κB p65 depletion and apoptosis. Similarly to what was reported for sea bass phagocytes, intoxication of mBMDM involves interaction of AIP56 C-terminal region with cell surface components, suggesting the existence of a conserved receptor. Biochemical approaches and confocal microscopy revealed that AIP56 undergoes clathrin-dependent endocytosis, reaches early endosomes, and follows the recycling pathway. Translocation of AIP56 into the cytosol requires endosome acidification, and an acidic pulse triggers translocation of cell surface-bound AIP56 into the cytosol. Accordingly, at acidic pH, AIP56 becomes more hydrophobic, interacting with artificial lipid bilayer membranes. Altogether, these data indicate that AIP56 is a short-trip toxin that reaches the cytosol using an acidic-pH-dependent mechanism, probably from early endosomes. Usually, for short-trip AB toxins, a minor pool reaches the cytosol by translocating from endosomes, whereas the rest is routed to lysosomes for degradation. Here we demonstrate that part of endocytosed AIP56 is recycled back and released extracellularly through a mechanism requiring phosphoinositide 3-kinase (PI3K) activity but independent of endosome acidification. So far, we have been unable to detect biological activity of recycled AIP56, thereby bringing into question its biological relevance as well as the importance of the recycling pathway.